Transforming growth: exposing the effects of salicylic acid and hydrogel (SAP) on mustard crops for increased yield and sturdiness (Journal of Oilseed Brassica, 2025)
The dry and semi-arid regions of the Indo-Gangetic plains have significant water-related difficulties. Brassica juncea, often known as mustard, is a resilient crop that flourishes during the rabi season and requires a reduced amount of water in comparison to other crops. A research study was conducted during the rabi season of 2020-21 to evaluate the effects of hydrogel SAP (Super Absorbent Polymer) and foliar spray of salicylic acid on different development stages of mustard crop. Based on research findings, the utilization of hydrogel @ 5.0 kg/ha, in conjunction with a foliar application of salicylic acid 200 ppm concentration, throughout the flowering and siliqua formation phases, had a significant impact on several yield characteristics. The aforementioned characteristics encompass seed yield (2613 kg/ha), stover yield (5435 kg/ha), soil moisture content (23.59%), relative water content in leaves, protein content and yield, SPAD value, proline, and NR B:C ratio (1.59). The utilization of hydrogel and salicylic acid has the potential to enhance the sustainable and efficient production and profitability of mustard crops in the arid and semi-arid regions of Haryana state of India.